The Multidimensional Work Motivation Scale: Validation evidence in seven languages and nine countries - Gagné, Marylène; Forest, J.; Vansteenkiste, M.; Crevier-Braud, L.; van den Broeck, A.; Aspeli, A.; Bellerose, J.; Benabou, C.; Chemolli, E.; Güntert, S.; Halvari, H.; Indiyastuti, D.; et al. (2015)
Self-determination theory proposes a multidimensional conceptualization of motivation comprising autonomous and controlled forms. Whereas autonomous motivation relates positively to individuals’ optimal functioning (e.g., well-being, performance), controlled motivation is less beneficial. To be able to use self-determination theory in the field of organizational behaviour, the Multidimensional Work Motivation Scale was developed and tested using data from 3435 workers in seven languages and nine countries. Factorial analyses indicated that the 19-item scale has the same factor structure across the seven languages. Convergent and discriminant validity tests across the countries also indicate that the psychological needs for autonomy, competence, and relatedness as well as the theoretically derived antecedents to work motivation (e.g., leadership and job design) are predictably related to the different forms of motivation, which in turn are predictably related to important work outcomes (e.g., well-being, commitment, performance, and turnover intentions). Implications for the development of organizational research based on self-determination theory are discussed.